THE EFFECT OF HEALTH EDUCATION ABOUT VULVA HYGIENE ON KNOWLEDGE OF PREVENTION OF URINARY TRACT INFECTION IN FEMALE STUDENTS - Selvia, Akub; Bura Mare, Agustina Chriswinda (Persatuan Perawat Nasional Indonesia (PPNI) Jawa Tengah, 2024)
The number of urinary tract sufferers is increasing, prevention of urinary tract infections can be held with vulva hygiene. The purpose of this study was to determine the effect of health education on vulva hygiene on knowledge of prevention of urinary tract infections (UTI) in class VIII female students at Ash Shiddiqiyyah Integrated Islamic Junior High School. The method used is quantitative research using experimental research design, with one group pretest-posttest design. Total sampling amounted to 39 respondents. The results of this study with data analysis conducted using the Wilxocon Test, there were pre-test results before health education about vulva hyginene regarding knowledge of prevention of urinary tract infections. The conclusion that Ha is accepted means that there is an effect of health education about vulva hygiene on knowledge of preventing urinary tract infections (UTI) in class VIII students at Ash Shiddiqiyyah Integrated Islamic Junior High School. Suggestions from this study are expected that the community can increase knowledge about vulva hygiene for the prevention of urinary tract infections